Effect of Simulation-Based Education on the Preparedness of Healthcare Professionals for the COVID-19 Pandemic: a systematic review and meta-analysis - Maheu-Cadotte, Marc-André; Lapierre, Alexandra; Fontaine, Guillaume; Mailhot, Tanya; Lavoie, Patrick (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: Healthcare organizations around the world have embraced simulation to prepare healthcare professionals to the COVID-19 pandemic. However, this pandemic implies additional educational challenges in rapidly designing simulation activities, while remaining compliant with health and safety measures to prevent the spread of the virus. The effect of simulation-based education in this context remains to be evaluated. Objective: The purpose of this systematic review was to describe the features and evaluate the effect of simulation activities on the preparedness of healthcare professionals and students to safely deliver care during the COVID-19 pandemic. Methods: Databases were searched up to November 2020 using index terms and keywords related to healthcare professions, simulation, and COVID-19. All learning outcomes were considered according to the Kirkpatrick model adapted by Barr et al. (2020). Reference selection, data extraction, and quality assessment were performed in pairs and independently. Results were synthesized using meta-analytical methods and narrative summaries. Results: 22 studies were included, 21 of which were single-group studies and 14 of those included pretest/posttest assessments. Simulation activities were mostly implemented in clinical settings using manikins for training on the use of personal protective equipment, hand hygiene, identification and management of COVID-19 patients, and work processes and patient flow. Large improvements in learning outcomes after simulation activities were reported in all studies. Discussion and conclusion: Results should be interpreted cautiously due to significant threats to the internal validity of studies and the absence of control groups. However, these findings are coherent with the overall evidence on the positive effect of simulation-based education. Future studies should include control groups if feasible.